(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about irrigated soils used in agriculture in the Gijduvan district of the Bukhara region. Irrigated agricultural land in the region amounts to 19.994 thousand hectares. It is said that 52.8% are meadow soils, 27.4% are desert-meadow soils, 13.7% are takyr-meadow soils, 3.3% are gray-brown and 2.8% are gray-brown-meadow soils. Information such as the level of salinity of irrigated soils with distribution by region, and the division of irrigated soils into groups according to mechanical composition are also presented. An agrochemical description of soils by layers was excavated on meadow soils scattered in the Omad farm of the Kh. Olimjon district of the Gijduvan region, the Shukur Tukhta farm of the Gulistan region and the Hasan Rajabi farm of S.Jabbarov. The mechanical structure area is illuminated. The agrochemical characteristics and mechanical composition of soils located in the same conditions are different and it has been stated that they have changed under the influence of various anthropogenic factors.